Unusual Cause of Gastrointestinal Bleeding in an Elderly Adult: Gastric Kissing Ulcers - , Osman Yüksekyayla, Ersin Batıbay, Cumali Efe (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Yüksekyayla O, Batıbay E, Efe C. Unusual cause of gastrointestinal bleeding in an elderly adult: Gastric kissing ulcers. Turk J Gastroenterol. 2024;35(5):421-422.